Community And Legal Right On Elderly Care - Amran Abdul Halim; Norazmi Anas; Amiruddin Mohd Sobali; Abdulloh Salaeh; Syed Najihuddin Syed Hassan; Mohd Izzuddin Agiman@Azman (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2024)
Indexed by ERA